2016
DOI: 10.1016/j.colsurfb.2015.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli as a model active colloid: A practical introduction

Abstract: The flagellated bacterium Escherichia coli is increasingly used experimentally as a self-propelled swimmer. To obtain meaningful, quantitative results that are comparable between different laboratories, reproducible protocols are needed to control, 'tune' and monitor the swimming behaviour of these motile cells. We critically review the knowledge needed to do so, explain methods for characterising the colloidal and motile properties of E. coli cells, and propose a protocol for keeping them swimming at constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
145
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(158 citation statements)
references
References 139 publications
(212 reference statements)
13
145
0
Order By: Relevance
“…In DDM experiments, the mean swimming speed was calculated from DDM movies as an average over ∼10 4 cells/ml. Details of the image processing and data analysis were as before [Wilson et al, 2011,Martinez et al, 2012,Martinez et al, 2014,Schwarz-Linek et al, 2016. DDM allows the measurement of an advective speed, simultaneously, over a range of spatialfrequency q, where each q defines a length-scale L=2*pi/q (for more details, see [Wilson et al, 2011, Martinez et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In DDM experiments, the mean swimming speed was calculated from DDM movies as an average over ∼10 4 cells/ml. Details of the image processing and data analysis were as before [Wilson et al, 2011,Martinez et al, 2012,Martinez et al, 2014,Schwarz-Linek et al, 2016. DDM allows the measurement of an advective speed, simultaneously, over a range of spatialfrequency q, where each q defines a length-scale L=2*pi/q (for more details, see [Wilson et al, 2011, Martinez et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…3D for all magnitudes of osmotic upshocks was previously characterized in Motility Buffer, where E. coli maintains Proton Motive Force (PMF) using endogenous energy sources [Dawes andRibbons, 1965, Schwarz-Linek et al, 2016]. At fixed buffer composition, the time it takes to consume all available oxygen is inversely proportional to the cell concentration, and upon oxygen exhaustion a sudden 'crash' in swimming speed occurs [Schwarz-Linek et al, 2016]. Interestingly, we do not see such a 'crash' in swimming speed for the lowest five values of the imposed upshock, but do see a 'crash' when the upshock is at the highest value of 785 mOsmol/kg.…”
Section: Osmotic Response Shows Osmokinesis Ie Changes In Motor Speedmentioning
confidence: 99%
See 1 more Smart Citation
“…The self-propelled particles can convert ambient or internal free energy into persistent motions with a direction depending on the local configuration of particles and interparticle interactions. Suspensions of swimming microorganisms and synthetic colloidal swimmers are the most widely studied active fluids in experiments and frequently serve as models for theoretical investigations [4,6]. Joint efforts of experiments, simulations, and theories have shown that active fluids exhibit surprising behaviors such as giant number fluctuations [7][8][9], ordered phases with collective particle motions [3,10,11], and abnormal rheology [12][13][14][15], unknown to conventional equilibrium complex fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Active fluids are a novel class of nonequilibrium soft materials, which are composed of a large number of selfpropelled particles suspended in simple fluids [1][2][3][4][5]. The self-propelled particles can convert ambient or internal free energy into persistent motions with a direction depending on the local configuration of particles and interparticle interactions.…”
Section: Introductionmentioning
confidence: 99%